(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Fungi used for the bio-recycling of marine residues, which isolated from the residues of marine organisms accumulated on shore .Marine remains of organisms were collected during the period 2015-2017. The work included physiochemical treatments and isolation of Fungi of each (Aspergillus niger, Aspergillus terreus, Trichoderma harzianum, Mucor circinelloides) from the shore are adapted to the accumulated residues. These Fungi are characterized by their ability to secrete an enzymatic spectrum that degrades the compounds in these residues and build their protein-rich biomass through their metabolism. Results of The study showed a clear increase in total protein Where It reached in mixed cultures (Trichoderma harzianum, Aspergillus niger) %(44.14)In a solid nutrient culture from the remains of marine organisms. Suggesting that high content of protein can be produced in a small area of space, time and under available conditions and disposal of these residues and access to economically important materials. استخدمت أنواع من الفطريات معزولة من بقايا الأحياء البحرية المتراكمة على الشاطئ في إعادة التدوير الحيوي لهذه البقايا البحرية، جمعت البقايا خلال الفترة الممتدة من 2015– 2017، تضمن العمل معالجات فيزيوكيميائية لها وعزل لفطريات Aspergillus niger, Aspergillus terreus, Trichoderma harzianum) , (Mucor circinelloidesمتأقلمة مع هذه البقايا المتراكمة. تتميز هذه الفطريات بقدرتها على إفراز طيف أنزيمي مفكك للمركبات الموجودة في هذه البقايا، وبناء كتلتها الحيوية الغنية بالبروتين من خلال استقلابها لهذه المركبات. أظهرت نتائج الدراسة ارتفاعاً واضحاً في نسبة البروتين، حيث بلغت في المزارع المختلطة بالفطرين (Trichoderma harzianum وniger Aspergillus) (44.14)% في وسط زرعي مغذي جامد من بقايا أحياء بحرية. مما يشير الى إمكانية إنتاج كميات كبيرة من البروتين في حيز صغير من المكان والزمان وضمن شروط متاحة، والتخلص من هذه البقايا والحصول على مواد هامة اقتصادياً.